Correlation of Total Sperm Count with Presence of Round Cells and Abnormal Sperm Morphology in Semen Analysis - Krishnamurthy, Thejasvi; R, Yashica Gowda (Annals of Pathology and Laboratory Medicine, 2019)
Background: Among the routine semen parameters, presence of round cells and morphological defects in sperms are important qualitative parameters in semen analysis. Detailing the "round cells" and qualitative defects in sperms becomes important as these factors affect fertility. In this study, we aim to categorise and assess the percentage of round cells and morphological defects of sperms in correlation with total sperm count. Methods: 70 random semen samples were included which were collected from males being evaluated for infertility. They were divided into two groups based on the total sperm count. Papanicolaou stained smears were studied for categorisation of round cells and qualitative defects in sperms .These were then correlated with total sperm count. Result: We observed that both the groups showed presence of round cells and morphological defects in sperms with a slightly higher percentage in reduced sperm counts. Round cells observed in our study included immature germ cells, leucocytes and epithelial cells. Frequent morphological defects were round head, large head and coiled tail. Conclusion: Round cells and morphologically defect sperms are frequently observed in semen samples with reduced sperm counts compared to normal sperm counts.